Faktor yang Mempengaruhi Kinerja Karyawan UMKM Enceng Gondok Dengan Etos Kerja Islam Sebagai Variabel Moderasi - Cicih Carcih; Diyah Ariyani (Institut Agama Islam Negeri Ponorogo, 2024)
This study aims to determine how work motivation, work environment and locus of control affect employee performance with work ethic as a moderating variable. This study is a quantitative study using primary data with a population of all water hyacinth craft UMKM craftsmen in Semarang Regency. The sampling technique using saturated samples produced 60 samples. The data collection method was carried out through distributing questionnaires and direct observation to water hyacinth craft UMKM in Semarang Regency. The data was processed using the IBM SPSS statistical tool version 26. Through the data analysis carried out, it showed that: work motivation has a positive and significant effect on employee performance, the work environment has a negative and insignificant effect on employee performance, locus of control has a positive and significant effect on employee performance, and Islamic work ethic is unable to moderate work motivation, work environment and locus of control on employee performance